BIMBINGAN KONSELING ISLAM DENGAN PENDEKATAN RASA SYUKUR DALAM MENINGKATKAN MOTIVASI BELAJAR - Enik Sartika (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
This study aims to explain the importance of gratitude in the counseling guidance process. Where when the client is grateful for every problem he is facing, he will feel good in the life that Allah has given him. a grateful person is someone who receives a gift and an appreciation and potential. With gratitude it will foster a sense of self-awareness that it is fortunate that we are still able to enjoy the level of education, so that it will strengthen individuals to continue learning towards a better future. Grateful people are able to identify themselves as conscious and grateful for God's gifts, gifts from others, and take the time to express their gratitude. The expression shown is by continuing to actively study and develop the potential that Allah has given him.